2010
DOI: 10.4102/jsava.v81i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasites of stray dogs impounded by the Society for the Prevention of Cruelty to Animals (SPCA), Durban and Coast, South Africa : short communication

Abstract: Coprological examination was used to determine the prevalence and intensity of gastrointestinal parasites of stray dogs impounded by the Society for the Prevention of Cruelty to Animals (SPCA), Durban and Coast, South Africa. Helminth and protozoan parasites were found in faeces of 240 dogs with an overall prevalence of 82.5% (helminth parasites 93.1% and protozoan parasites 6.9 %). The following parasites and their prevalences were detected; Ancylostoma sp. (53.8 %), Trichuris vulpis (7.9 %), Spirocerca lupi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
8
11
0
1
Order By: Relevance
“…Our findings like in other studies 33,35 detected more helminth ova (Ancylostoma sp, Toxocara sp, Uncinaria sp and Strongyloides sp) than protozoan oocysts (Isospora). The disparity could be due to the fact that helminth ova are more effectively transmitted to stray dogs and could survive better in the environment than protozoan oocyst.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings like in other studies 33,35 detected more helminth ova (Ancylostoma sp, Toxocara sp, Uncinaria sp and Strongyloides sp) than protozoan oocysts (Isospora). The disparity could be due to the fact that helminth ova are more effectively transmitted to stray dogs and could survive better in the environment than protozoan oocyst.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in Nigeria 29,30,31,32 and in other regions of the world 13,33,34 similarly reported high level of GI infection in stray/roaming dogs. These findings affirm that environmental pollution with faeces of stray/roaming dogs is a public health concern and constitutes health hazard to human population.…”
Section: Discussionmentioning
confidence: 76%
“…The highest T. canis and T. cati infection rates in Asia were dedicated to Russia and China with 63 and 36.5%, respectively [54,55]. Additionally, mild Toxocara species infections were identified in African domestic carnivores [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with data from other studies (Palmer et al, 2007;Traub et al, 2004), A. caninum appears to be the dominant species. The presence of Ancylostoma species in dogs poses a risk to humans of acquiring zoonoses, although human cases have not been investigated in Durban (Mukaratirwa and Singh, 2010). An increase in the sample size will yield more reliable prevalence rates, and may reveal the presence of further Ancylostoma species in the region.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed a relatively high prevalence of Ancylostoma spp. in dogs in Southern Africa (Mukaratirwa and Busayi, 1995;Minaar et al, 2002;Mukaratirwa and Singh, 2010). These species affect not only dogs, but also humans, and hence are of zoonotic importance (Traub et al, 2004).…”
Section: Introductionmentioning
confidence: 99%